Nowa instrukcja Konferencji Episkopatu Polski o muzyce kościelnej (2017) - Tyrała, Robert (Studia Pastoralne, 2026)
During its meeting on 14 October 2017 in Lublin the Polish Episcopal Conference issued a new instruction on church music which has been being introduced in the Polish dioceses since that day. It is worthwhile to mention that the former and the first Instruction of the Polish Episcopate on Liturgical Music after the 2nd Vatican Council was issued in 1979, be the result of the conciliar revival of liturgy and music incorporated in it. This first instruction was approved in the context of post-conciliar reform, and from the time perspective it proved its expediency although in certain points it was certainly not uniformly and fully observed whereas in others somewhat outdated. The new Instruction of the Polish Episcopal Conference on Church Music was preconditioned by the church musicians from all over Poland who are the members of the Association of Church Musicians, and was later perfected by the Sub-Commission of Church Music of the Polish Episcopal Conference. To produce the Instruction in its final form the voices of the bishops responsible for the liturgy and music in the Polish dioceses were carefully considered. Preparation of the new Instruction lasted over 5 years and it is history which will judge whether all the matters were properly dealt with. We can say with absolute certainty that no instruction is able to resolve all the problems which occur in the daily preparation of liturgy and liturgical music. However, the instruction has surely every chance to re-settle certain matters of the entire Polish Church which is what probably the bishops were counting on while approving this document. The new Instruction consists of 12 chapters, introduction and summary. It encompass 66 points with numerous sub-points. The successive chapters are: I. General Rules; II. Musical Functions in Liturgy; III. Music in the Liturgy of the Holy Mass; IV. Music in Liturgical Year; V. Singing the Liturgy of the Hours; VI. Music in the Liturgy of the Holy Sacraments and Sacramentals and during Services; VII. Music in Liturgy Broadcast by Media; VIII. Instrumental Music; IX. Songbooks and Supporting Materials; X. Concerts of Religious Music; XI. Musical Education and Formation; XII. Commissions of Sacred Music and Other Supporting Organizations. All of these issues are thoroughly discussed in the Instruction with a very important note at the end, in which we can read: “[…] the bishops encourage the Polish Association of Church Musicians to prepare a detailed commentary to this Instruction, amongst those the most desirable ones seem to all explanations and focus on all the aspects of the pastoral care of the Church for sacred music” (Instruction of the Polish Episcopal Conference on Church Music, no. 64). The above mentioned note seem particularly important due to the fact that it is impossible to include everything in one document so as to make it substantive and concise. Therefore the Polish Association of Church Musicians, which initiated this new norm in the Polish Church, is about to add the required commentary. It seems a good and proper way of procedure. This article presents the New Instruction in its entirety so as to demonstrate its tremendous role. It also discusses the problems included in the said document. The choice of the subject and its rendition in the jubilee book of Rev. Professor Antoni Reginek PhD Habilitatus stem from the fact that the jubilee celebrator is one of the creators of the Instruction – first as the Chairman of the Polish Association of Church Musicians, then as a Consultant of the Sub-Commission for Church Music – thus it seems perfectly logical that the topic is meaningful and important to him. The author’s wish is to make this article a peculiar kind of tribute paid to the Reverend Professor himself and the token of immense gratitude for Rev. Reginek’s knowledgeability, benevolence and inestimable, friendly and long-lasting cooperation to be hopefully continued in the future.